(untitled) (Agroindustria, Sociedad y Ambiente, 2020)
Renewable energy, also called green energy, has reached 40% worldwide due to the fact that every year governments promote its development, which helps to reduce the burning of fossil fuels and CO2 emissions, the main causes of environmental pollution. Among the alternative sources of clean energy is solar energy, whose alternative is feasible in Ecuador, since being a tropical country allows the generation of electricity from solar radiation, which is estimated at 4.5 kw m2 d-1. The objective of this work was to design a solar energy module to partially replace the use of conventional energy sources and minimize CO2 emissions, in the operation of the monitoring and surveillance system of the University of the Armed Forces of Ecuador (ESPE) in Latacunga, Cotopaxi. The results found show that the solar modules used can generate a load of 100W per day, guaranteeing an energy supply of 4 hours. Although the operation of the solar panel system was optimal from the operational point of view, the amount of energy generated was not sufficient to meet the daily requirements of Ecuadorian households. Although the development of modules with greater capacity to generate energy would lead to a considerable reduction in CO2 emissions, the mass use of this type of energy source could be limited by the high cost of installation and low prices of electricity in Ecuador.